Spatio-temporal evolution of pulsating aurora observed using a ground-based imagers - Pandya, Megha; Bhaskar, Ankush; Samara, Marilia; Michell, Robert; Mirizio, Emma; Kang, Suk-Bin; Blum, Lauren W. (Frontiers in Astronomy and Space Sciences, 2025)
We investigated the pulsating aurora observed on 7 January 2014, by a narrow field-of-view (FOV) high-time resolution ground-based white-light imager and all-sky low-time-resolution imager operated at Poker Flat, AK (geographic: 65.1°N, 147.4°W). The pulsating aurora showed very notable characteristics, such as frequency drift in their pulsation with time and drifting of the entire pulsating auroral structure in space. We find that (i) the entire pulsating auroral patch was observed to drift northward at a velocity of approximately 76 m/s, which aligns closely with the local convection velocities obtained from Super Dual Auroral Radar Network (SuperDARN) data, consistent with the idea that the patch motion is primarily due to E×B convection. (ii) The duration of persistence for each pulsation in the pulsating aurora is found to be ∼1 s (iii) The auroral pulsation frequency abruptly increases from ∼0.0625 Hz to ∼0.5 Hz, closely aligning with the broadening of the frequency band observed at the Dawson (DAWS) ground magnetometer location. Wavelet analysis of DAWS magnetic field data, recorded at similar magnetic local time (MLT) and L-values, reveals the presence of Pc-1 geomagnetic pulsation (Pc-1). This connection suggests that the drift in auroral pulsation frequency may be driven by the evolution of Pc-1 waves, which are influenced by changes in the local plasma environment. The broadening of the frequency band may indicate dynamic variations in magnetospheric ion composition or plasma density. This interplay underscores the role of Pc-1 waves and magnetospheric dynamics in determining the auroral pulsation characteristics.